Populärvetenskapligt skrivande vidgar perspektivet och ökar förståelsen - Susanne Pelger (Högre Utbildning, 2011)
The capacity to explain subject matter to a non-specialist audience is one of the highest valued generic skills among science alumni of Lund University. Despite this fact, popular science communication is only poorly practiced during the undergraduate studies. In an earlier study we analysed the quality of popular science papers written by degree project students of biology. Our major observation was that most students had difficulties in changing perspectives, and in arguing the importance and relevance of their findings. In the project report we discussed the potential of popular science writing as a didactic tool. This is the main issue of the present article, which focuses on students’ own experiences of writing for the general public.